2018
DOI: 10.7717/peerj.5410
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of obesity, metabolic syndrome, and type 2 diabetes: amino acid and acylcarnitine levels change along a spectrum of metabolic wellness

Abstract: BackgroundMetabolic syndrome (MS) is a construct used to separate “healthy” from “unhealthy” obese patients, and is a major risk factor for type 2 diabetes (T2D) and cardiovascular disease. There is controversy over whether obese “metabolically well” persons have a higher morbidity and mortality than lean counterparts, suggesting that MS criteria do not completely describe physiologic risk factors or consequences of obesity. We hypothesized that metabolomic analysis of plasma would distinguish obese individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
94
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 88 publications
15
94
2
Order By: Relevance
“…The decreased ADMA after OAGB ( Table 2) suggests that this surgical procedure can lead to decreased cardiovascular risk in patients. Some authors [9,12,14] observed elevated levels of lysine in patients before BS compared to levels in LCs; however, we observed lower levels of lysine in obese subjects and its impact on the biotin metabolism (7.55E06, impact 0.00; Table S2) and lysine metabolism (p < 0.0001, impact 0.10; Table S2) pathways ( Figure 3A). After OAGB, the levels of lysine were even lower than before in our patients.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The decreased ADMA after OAGB ( Table 2) suggests that this surgical procedure can lead to decreased cardiovascular risk in patients. Some authors [9,12,14] observed elevated levels of lysine in patients before BS compared to levels in LCs; however, we observed lower levels of lysine in obese subjects and its impact on the biotin metabolism (7.55E06, impact 0.00; Table S2) and lysine metabolism (p < 0.0001, impact 0.10; Table S2) pathways ( Figure 3A). After OAGB, the levels of lysine were even lower than before in our patients.…”
Section: Discussioncontrasting
confidence: 52%
“…It also plays a role in anemia, has an impact on the uptake of iron, and increases ferritin in blood [50]. Lysine is also a precursor of α-aminoadipic acid (AAD) formed during lysine degradation [12]. It seems that in our group of patients, catabolism of lysine is elevated; however, we did not investigate the AAD levels.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is tempting to speculate that the increased levels of cysteine in high glucose extracellular fluid are due to the well-known oxidative stress induced by high glucose in proximal tubular cells [17], which leads to a disulfide bond by the oxidation of two molecules of cysteine and the consequent formation of cystine. This dipeptide can inhibit tyrosine aminotransferase activity and can lead to an increased plasma tyrosine level [52,53]. This is exactly what we have observed in our study.…”
Section: Biological Interpretation Of the Resultssupporting
confidence: 88%
“…Methionine sulfoxide is an indicator of oxidative stress. Increased kynurenine and alpha-AAA are associated with increased immune functions and metabolic dysfunctions, respectively [24]. The serum levels of serotonin significantly increased and the levels of creatinine and dopamine significantly decreased in infected RD mice compared to uninfected RD mice (Figure 4(b)), whereas the levels of sarcosine and putrescine significantly increased and serotonin significantly decreased in infected HFD mice compared to uninfected HFD mice (Figure 4(b)).…”
mentioning
confidence: 96%